KARAKTERISTIK DAN MUTU ORGANOLEPTIK FISH CRACKERS SNACK FOOD - Hendrayati Hendrayati (Media Gizi Pangan, 2020)
ABSTRACT Rapid city growth can change the existing social fabric, including the lifestyle and diet of the urban population. The period before the massive urbanization of diet is determined by food prices and family purchasing power and mother's knowledge about nutrition and health. Currently eating patterns lead to increased consumption of snacks. Fish craker snack food is an alternative food supply in the form of snacks with the main ingredients as white anchovy (stelpohorus, sp), so that high quality snacks are obtained from nutritional quality, safe for consumption and high organoleptic quality. Fish snack craker food is a processed food made from anchovy with a dry, crispy texture. Fish processing in this way aims to sustainably benefit fish, produce healthy, safe, whole and halal foods and be accepted by consumers according to current market tastes. In making fish crackers snack food design used is the manufacture of products in 4 compositions, namely origional products, the addition of anchovies flour (stelpohorus sp) 30%, 40% and 50% Fish cracker snack food is a safe snack to consume where the proximate character results are good on average, trans fatty acids